Albert Camus: Temporality and Human Nature - Silva, Gabriel Ferreira da (2015)
In this paper we present some aspects of the analysis of temporality that Albert Camus gave using the ideas of The Absurd and Revolt, above all with respect to how they mark a possible path for his development of the concept of Human Nature. This concept was fundamental for his human ontology which itself formed the basis for his whole ethical, aesthetical, and metaphysical thought.